2014
DOI: 10.1177/1077546314534715
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-mechanical vibration and instability of carbon nanocones conveying fluid using nonlocal Timoshenko beam model

Abstract: In this paper, thermo–mechanical vibration analysis of carbon nanocones (CNCs) conveying fluid based on nonlocal elasticity theory is investigated. The governing equations are developed using Hamilton’s principle and a general eigenvalue problem is obtained by discretizing the resulting equations using the finite element method. In this paper, the non-uniform cross-section Timoshenko beam theory is utilized and the influences of apex angle, top radius, length, temperature change, thickness, small-scale paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 40 publications
0
4
0
1
Order By: Relevance
“…They showed that the effects of nonlocal effect, viscosity of fluid, boundary conditions, and curvature on the behavior of curved CNTs and straight CNTs are the same. Afkhami and Farid (2014) reported the vibration and instability of fluid-conveying carbon nanocones based on nonlocal elasticity theory and thermal elasticity. The results showed that the nonlocal Timoshenko beam theory predicts smaller critical flow velocity rather than the classical theory.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the effects of nonlocal effect, viscosity of fluid, boundary conditions, and curvature on the behavior of curved CNTs and straight CNTs are the same. Afkhami and Farid (2014) reported the vibration and instability of fluid-conveying carbon nanocones based on nonlocal elasticity theory and thermal elasticity. The results showed that the nonlocal Timoshenko beam theory predicts smaller critical flow velocity rather than the classical theory.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the small-size effects and Knudsen number, the vertical nanotube conveying fluid was studied by Bahaadini et al [40] based on the nonlocal strain gradient Timoshenko beam theory. A thermo-mechanical vibration instability analysis of the CNT conveying fluid was conducted by Afkhami and Farid [41] using a nonuniform cross-section nonlocal Timoshenko beam model. Besides a linear stability analysis, nonlinear vibration characteristics have also been focused on by researchers.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is verified that temperature change and magnetic field could also impact upon the vibration of CNTs [44][45][46][47][48][49][50][51][52][53][54][55][56]. Considering the thermal and surface effects, Zhen and Zhou [57] utilised the Euler-Bernoulli beam model and non-local strain gradient theory to analyse the properties of wave propagation in fluid-conveying SWCNTs under magnetic field.…”
Section: Introductionmentioning
confidence: 99%